Victimización de los delitos de odio: aproximación a sus consecuencias y a las respuestas institucional y social = Hate Crimes Victimization : approximation to its Consequences and to the Institutional and Social Responses - Otaolaurruchi, Pedro Achutegui (Revista de victimología, 2017)
Conformity and tolerance with regard to stereotypes and prejudices have contributed to desensitize to a society which looks for in "the others" the justification of its own problems. Rumours and hate speech stimulate an intolerance that ends up leading, in many times, in discriminatory acts or in hate crimes. The seriousness of these facts comes determined because the discrimination transgress principles such as equality before the law, equal treatment or equal opportunities, while hate crimes attack to the principle of dignity, that is, to the value of the person as such, and to the universality of human rights and the principles that they contain. Face to these crimes the society has begun to react by creating partnerships that are sometimes grouped into networks to optimize economic, social and legal resources. Also the institutions have being aware of the need to act quickly to preserve the integrity of victims who, often, confront the double circumstance of being simultaneously "victims of risk" and "especially vulnerable victims". At the social and institutional level, the main outstanding issues to combat this scourge are: sensitization, awareness and training.